Reforms under Fiscal Stress : A Policy Note on the Priorities for Fiscal and Budget Reform in Nepal - Bajracharya, Roshan Darshan; Biletska, Nataliya; Rajaram, Anand (World Bank, Washington, DC, 2013)
This note, first of the several on fiscal management and policy option notes planned, provides a concise assessment of the achievements to date of the ongoing reforms to budget management in Nepal and concludes with some guidance on the key focus areas of fiscal policy and expenditure management over the near and medium term. It is a selective assessment that looks at major aspects of the policy and budget process with a view to identifying areas for strategic focus, rather than a detailed rendering of the reforms. The note highlights the fiscal challenges that are assuming increasing prominence and which must be addressed by policy decisions and medium term reforms. While recognizing the uniqueness of Nepal's initial conditions, capacities and current security related challenges, the note takes account of international experience in implementing such reforms. The note starts with the economic and political background. The second section reviews fiscal trends and outlines issues to be considered by a fiscal strategy. The third section discusses institutional issues to strengthen the budget process.